Studi Analisis Struktur Living Quarter Pada Floating Production System di Perairan Lepas Pantai Indonesia - Pramana, Dewa Ketut Surya; Nurlina, Siti; Waluyohadi, Indra; Hidayat, M. Taufik (Rekayasa Sipil, 2018)
Offshore Unit is one of vital infrastructure in gas and oil production. There are many kind of offshore structure which use in gas and oil industry, one of it is a Floating Production System. Floating Production System is system where a modified tanker ship uses by the company of gas and oil to process hydrocarbon, nature gas, and oil. Technically FPS is a tanker ship that produce gas and oil nut can not storage directly while producting, that’s why there must be another storage ship while the tanker ship producing. In this living quarter structure analysis constitute on structure analysis in transportation condition. In this living quarter structure analysis utilize SAP2000 V.19 software which obtain bigest moment, shear, and axial from 8 different wave direction that accepted by the ship’s hull. Output software analysis and manual analysis shown that main steel structure of living quarter capable hold the loads that applied, which is structure load, dead and live load, wind load, and acceleration load.